Diterpene esters of aristolochic acids from Aristolochia pubescens - Nascimento, I. R.; Lopes, LMX (Elsevier B.V., 2003)
From the acetone and ethanol extracts of the tubercula of Aristolochia pubescens, two diterpene esters of aristolochic acids were isolated, together with 23 known compounds. The structures of the compounds were determined on the basis of spectroscopic analysis. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: Aristolochia pubescens; Aristolochiaceae; diterpene esters; aristolochic esters; aristolochic acids; kaurane diterpenes; lignans